2013
DOI: 10.3109/00016489.2013.788791
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of intratympanic prednisolone injection in patients with idiopathic sudden sensorineural hearing loss

Abstract: The comparison of audiometric data at study entry, at 10 days, and at 1 year after the treatment showed a statistically significant improvement of the mean pure tone audiometry. The evaluation of the hearing outcomes demonstrated a statistically significant improvement, with similar success rates when evaluated 10 days and 1 year after the treatment. Comparing the hearing outcomes at 1 year with the results at 10 days, no significant difference was detected between these two time points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
11
0
3
Order By: Relevance
“…Studies in animal models have already highlighted the neural pathways through which the trigeminal afferents may interact at the level of the central nervous system 21,22 . The trigeminal input, through the Gasser ganglio and the trigeminal nuclear complex, reaches the dorsal cochlear nucleus (DCN) 23 , and may affect the activity of the central sound 24 , especially in situations of concomitant cochlear damage. Moreover, in patients suffering from tinnitus, it has been shown that the intensity of the symptom can be modulated by a somatosensory stimulation (electrical stimulation of the median nerve at the wrist) 24 , an experience that is interpreted as non-specific activation of nerve structures in the process of extra-lemniscal tinnitus genesis 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies in animal models have already highlighted the neural pathways through which the trigeminal afferents may interact at the level of the central nervous system 21,22 . The trigeminal input, through the Gasser ganglio and the trigeminal nuclear complex, reaches the dorsal cochlear nucleus (DCN) 23 , and may affect the activity of the central sound 24 , especially in situations of concomitant cochlear damage. Moreover, in patients suffering from tinnitus, it has been shown that the intensity of the symptom can be modulated by a somatosensory stimulation (electrical stimulation of the median nerve at the wrist) 24 , an experience that is interpreted as non-specific activation of nerve structures in the process of extra-lemniscal tinnitus genesis 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Gundogan et al, for example, advocated a 1‐month follow‐up, Battaglia et al a 2‐month follow‐up, Filipo et al a specific (1‐year) long‐term follow‐up, and Fushiki et al a nonspecific long‐term follow‐up . We chose a 2‐month follow‐up time because < 8% of patients are expected to experience further hearing improvement after 2 months . However, improvement may occur in the chronic phase of ISSNHL after therapy for comorbid Hch …”
Section: Discussionmentioning
confidence: 99%
“…The follow-up period after the initiation of treatment for ISSNHL varied in other reports. Gundogan et al, 38 for example, advocated a 1-month follow-up, Battaglia et al 39 a 2-month follow-up, Filipo et al 40 a specific (1-year) long-term follow-up, and Fushiki et al 41 a nonspecific long-term follow-up. 42 We chose a 2-month follow-up time because < 8% of patients are expected to experience further hearing improvement after 2 months.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In combination with HBOT, the overall success rate of ITS was superior when compared to i.v. steroid application . However, HBOT in addition to application of a vitamin cocktail and dexamethasone, did not improve chronic ISSNHL in another study .…”
Section: Introductionmentioning
confidence: 92%